Financial statement analysis - Wild, John J.; Bernstein, Leopold A; Subramanyam, K.R. (Bostone : Irwin/McGraw-Hill, 2001)
Business
2002-06-10
Keywords: Financial statements; Accounting analysis; Financial analysis